Comparison of rain prediction models to be used in the equatorial region - Mohd Ansor Yusof, (1997)
Rain will cause serious attenuation on microwave signals transverse in the atmosphere. Rain attenuation strongly depends on rain attributes. This paper reports the comparison of three models of ]-min. rain rate cumulative distribution for estimating signal attenuation due to rain in the equatorial region. The models are Rice-Dutton (RHDD) model, Tattelman-Scharr (TS) model and Moupfouma model